ACTIVITIES OF HEALTH CARE AND REHABILITATION INSTITUTIONS FOR PERSONS INJURED IN THE WAR AS A GUARANTEE OF SOCIAL AND ECONOMIC SECURITY OF THE REGION - KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines in detail the problem of the impact on the state of socio-economic security of Regions and the state as a whole of measures for the rehabilitation of war victims. It is established that the creation of a set of necessary conditions for ensuring full rehabilitation of various categories and groups of persons affected by war is a prerequisite for ensuring the socio-economic security of the state as a whole and each of its regions separately, taking into account their existing potential, available opportunities and specific conditions for implementing appropriate measures. The main functional components of socio-economic security of the regions are identified. The article substantiates the claim that achieving the necessary level of socio-economic security of the region, especially in the context of modern challenges and threats, is possible only as a result of their comprehensive consideration and effective management. The need for a radical revision of the principles and approaches in the organization of the rehabilitation system and the provision of social guarantees to the population is proved, which will determine the introduction of new models of organization, administration and management, the use of a fundamentally different methodology for assessing the quality of the results of the rehabilitation process, as well as the process of social adaptation. The key principles on which modern systems of providing rehabilitation and social services should be based are highlighted. It is established that extreme situations of a social nature are determined primarily by the socio-economic component of society. Employment policy opportunities are not fully used at the regional level, and one of the most acute socio-economic problems, the solution of which is the responsibility of the regions, is to provide the population with affordable and social housing. However, due to significant imbalances in their development, not all of them are able to independently and fully ensure their own socio-economic security. The main priorities for ensuring the socio-economic security of the state and its regions in war conditions are outlined.